Seasonal variation of precipitable water vapour in the atmosphere over India - ANANTHAKRISHNAN, R.; SELVAM, M. MARY; CHELLAPPA, R. (MAUSAM, 1965)
Based on the upper air data for the six-year period, 1956 to 1961, the mean monthly precipitable water vapour at 12 Indian radiosonde stations have been calculated. The seasonal and diurnal variations of precipitable water vapour and. its relation to mean monthly rainfall have been discussed.